Pentingnya Peningkatan Kompetensi Bahasa Inggris bagi Guru Anak Usia Dini - Niswatin Nurul Hidayati (Universitas Al-Hikmah Indonesia, 2018)
Fromkin et al. (1990) stated that English has been called “the lingua franca of the world”. Because of that, mastering the language could be considered as an obligation in order to survive in the global and technology era. Indonesian government has realized the matter, so that the language is included in its education system. Some experts mentioned that it is better to start learning foreign language in the early childhood since there are some advantages could be achieved, such as intellectual improvement, mother tongue improvement, and Cultural gains. Knichalova (2011) stated that it is said that children absorb language like a sponge. It happens when they were in a period known as Golden Age. Due to the matter, a teacher plays big role in early childhood education, including English learning. So, improving the capability and competency of early childhood teachers, especially in English could be as said as an obligation also because a teacher is a role model for his/her students in a learning process.